Pengaruh Pengetahuan Pajak Terhadap Kepatuhan Pajak pada UMKM di Kecamatan Sangalla Utara - Mesi Pabetta; Ade Lisa Matasik; Grace Sriati Mengga (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The aim of this research is to determine the effect of tax knowledge and tax sanctions on tax compliance among MSMEs in North Sangalla District. The data analysis techniques used are descriptive analysis, data quality assessment, classical assumption testing. Based on the results of this research, it shows that tax knowledge has a positive and significant effect on MSME taxpayer compliance in North Sangalla district. This is shown by the tcount value of 3.679>ttable 1.987, with a significance value of 0.000<0.05. Based on the results of this research, it shows that tax sanctions have a positive and significant effect on the compliance of MSME taxpayers in North Sangalla District. This is shown by the tcount value of 2.443>ttable 1.987, with a significance value of 0.0017<0.05. Based on the results of this research, it shows that tax knowledge and tax sanctions have a positive and significant effect simultaneously on taxpayer compliance of MSMEs in North Sangalla District. with a calculated F value of 26.140 > F table 2.71 with a significance of 0.000,